2015
DOI: 10.1002/smll.201500210
|View full text |Cite
|
Sign up to set email alerts
|

Large Single-Crystal Hexagonal Boron Nitride Monolayer Domains with Controlled Morphology and Straight Merging Boundaries

Abstract: Hexagonal boron nitride monolayers with domain sizes up to 700 μm2 and geometry from triangle to hexagon are fabricated through a refined control over the precursor and morphology of the copper substrate. Hydrogen etching is shown to tailor the h‐BN monolayers precisely along the grain boundaries, providing their morphology over micro­meter scale and a new avenue toward fabricating nanoribbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 33 publications
(66 reference statements)
4
77
1
Order By: Relevance
“…: The domain sizes of CVD grown h‐BN were typically in the order of micrometer . Reducing the precursor feeding rate proves to be an efficient route to increase the domain size of h‐BN grown on Cu . We recently showed that when the partial pressure of the gas precursor decomposed from ammonia borane was lowered from 3 Pa to 0.4 Pa, the average domain size increased from less than 1 μm to larger than 20 μm on the inside surface of a Cu tube ( Figure a–c) .…”
Section: Synthesis Properties and Applications Of Two Dimensional H‐bnmentioning
confidence: 99%
“…: The domain sizes of CVD grown h‐BN were typically in the order of micrometer . Reducing the precursor feeding rate proves to be an efficient route to increase the domain size of h‐BN grown on Cu . We recently showed that when the partial pressure of the gas precursor decomposed from ammonia borane was lowered from 3 Pa to 0.4 Pa, the average domain size increased from less than 1 μm to larger than 20 μm on the inside surface of a Cu tube ( Figure a–c) .…”
Section: Synthesis Properties and Applications Of Two Dimensional H‐bnmentioning
confidence: 99%
“…Variations in the chemical potential of constituent elements can occur experimentally when different processes and substrates are used or when the Cu substrates are subjected to a pretreatment (i.e., oxidation) (Zhang et al, 2016), as in this scenario. To date, several other experimental approaches to obtaining similar hexagonal-shaped domains have been reported (Stehle et al, 2015;Tay et al, 2016b;Wang et al, 2015a;Wu et al, 2015;Yin et al, 2015b). The coexistence of ZZ N and ZZ B edges is further verified by the observation of truncated triangular-shaped domains (Fig.…”
Section: Geometric Shapes and Edge Assignmentsmentioning
confidence: 78%
“…Group 15 monolayers become another kind of attractive twodimensional (2D) materials after graphene 1, 2 hexagonal BN, [3][4][5][6] and transition metal dichalcogenides, [7][8][9][10][11] due to their appropriate band gap and high carrier mobility. 12 Zhang et al 12 predicted that the group 15 monolayers, namely phosphorene, arsenene, antimonene, and bismuthene, exhibit high thermodynamic stability and show a broad range of band gap from 0.36 to 2.62 eV.…”
Section: Introductionmentioning
confidence: 99%